Recent advances in the management of chronic ankle instability - Yimeng Yang; Yang Wu; Wenhui Zhu (Chinese Journal of Traumatology)
Ankle sprains are the most common lesion of the ankle joint which might result in chronic ankle instability (CAI). Significant strides have been taken to enhance our comprehension of the underlying mechanisms of CAI, as the exploration of novel surgical techniques and the identification of previously unrecognized anatomical components. The present review aims to provide an extensive overview of CAI, encompassing its pathophysiology, epidemiology, clinical assessment, treatment, and rehabilitation. Treatment of CAI requires a multifaceted algorithm, involving historical analysis, clinical evaluations, and diagnostic imaging. Surgical interventions for CAI primarily involve the anatomical and/or non-anatomical reconstruction and/or repair of the anterior talofibular ligament. Anatomical repair has exhibited superior functional outcomes and a reduced risk of secondary osteoarthritis compared to non-anatomical repair. Non-anatomical approaches fall short of replicating the normal biomechanics of the anterior talofibular ligament, potentially leading to postoperative stiffness. This review seeks to academically review and up-to-date literature on this issue, tailored for clinical practice, with the intent of aiding surgeons in staying abreast of this critical subject matter.